Afro-paisagens e hibridização cultural: dos carnavais atlânticos aos afoxés de Fortaleza/CE - Silva, Lidia Marques da (2023)
The present study corresponds to the characterization of the Fortaleza Afoxé, as a grouping of African and carnival traditions responsible for the celebratory manifestation of Candomblé and Umbanda temples in public spaces. We used the vectorial forces proposed by Oliveira (2012) to understand how they operate in the visibility and invisibility of the manifestation. Considering the hybridism and singularities of this expressiveness and its constituent connection with the matrices of the so-called Atlantic Africa, we will identify the ritualistic and imagistic elements present in African Atlantic carnivals and in the Atlantic Afoxé of northeastern Brazil, with the aim of understanding how the reverberations of these elements occurred in cultures that have points of convergence and divergence in their cultural fusions. In this sense, the objective of the work is to understand the Afro-landscapes of the Fortaleza Afoxé, taking into account the vectorial forces and the ancestral and hybridized connections with the carnival festivities of Atlantic Africa and the northeastern Afoxé groups, in order to provide documentary references and academic support that contribute to the dissemination of information about the existence of the manifestation in the city and its Atlantic connections. To achieve the proposed objectives, we used various methodological instruments: (1) Bibliographic research, through the analysis of academic texts, electronic newspapers, and general news websites. (2) The use of social media, such as Instagram, Twitter, and WhatsApp, for communication and monitoring of the analyzed parades. (3) Qualitative interviews with organizers of the groups in the city. The Afoxé is, therefore, an expressiveness born from cultural hybridizations, which has representative elements of an Atlantic-Fortaleza African identity, and is presented in this work as a path to understand these facets on a local scale. On the other side of the Atlantic, we also have carnivals that demonstrate how African countries are spaces for cultural reinventions and not just points of origin to explain performative traditions of the diaspora.